A ; Creation of Agricultural Land Market in Ukraine: Current State of Development - Vladimir Melnychuk; Sergiy Parkhomenko; Alexej Lissitsa (Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2005)
14 - . - - : , , - , - .. " " - - . - - . – – Land reform started in Ukraine 14 years ago became one of the most important issues in transformation of large state agricultural enterprises into market oriented agricultural enterprises. Significant changes in land use and land ownership has happened as a result of land reform implementation in Ukraine. Namely, state monopoly on land was eliminated, agricultural land was privatized, citizens of Ukraine received land plots in possession, first land transactions have happened at agricultural land market etc. Actual data regarding Ukrainian land relations reformation is systematized in this Discussion paper with especial focus on establishing the prerequisites of further formation and perspective development of the agricultural land market in Ukraine. Additionally, a current situation is described at the Ukrainian agricultural land market and its legislative regulations.
urn:nbn:de:gbv:3:2-4800
Keywords: O13; O17; P26; P32; P48; Q15; Q18; 330